Consumer Decision-Making Toward Ultra Milk UHT Product: The Role of Brand Image, Price Perception, and Product Quality in Magetan Regency, Indonesia - Meiliasari, Ditha; Supriyono, S. (Manunggal Halim Jaya, 2026)
This study analyzes the influence of brand image, price perception, and product quality on consumers' Ultra Milk UHT purchasing decisions in Magetan Regency. A quantitative descriptive approach was used, involving 85 respondents selected through convenience sampling. Data were analyzed using the Partial Least Squares (PLS) method with SmartPLS software. The findings show that brand image, price perception, and product quality each positively and significantly affect purchase decisions. These results provide strategic implications for the company to enhance brand strength, align pricing with consumer perceptions, and consistently maintain product quality in a competitive UHT milk market.